Masyarakat Muslim di Negara Brunei Darussalam: kajian mengenai isu dan cabaran dalam pemikiran Islam era globalisasi - Wan Ali, Wan Zailan Kamaruddin (Department of Southeast Asian Studies, Faculty of Arts & Social Sciences, University of Malaya, 2009)
Negara Brunei Darussalam has stated that it applies Melayu Islam Beraja as slogan and motto. The position and importance of Islam is understood as it is considered the official religion of the state. The status of Islam as clearly stated in the Constitution of Negara Brunei Darussalam (NBD) shows that its position is highly regarded by muslim society in Brunei. This article aims to study the major and minor issues related to Islam and the challenges towards Islam in the current situation. The findings are very important because it can be used as comparison to other countries in the region. It also aims to tackle issues related to Islamic Thought that comprises many sub-topics for instance theology, theosophy, comparative and several others. The issue concerning the methodology will also be discussed and examined in order to have a clear idea on how the issue is solved and what is the perspective or way of solving the problems applied by the authorities in Brunei as compared to others. At the end, its impact on muslim mind in Brunei will be highlighted and the challenges that they face will be thoroughly examined.